BUSINESS PROCESS REENGINEERING AND SERVICE DELIVERY IN HUDUMA CENTERS IN KENYA - Kamau, Florence; Rotich, Gladys; Ogollah, Kennedy (European Journal of Business and Strategic Management, 2022)
Purpose: Most public service institutions are generally different in design and operation compared to several years back. The advances in technology and consumer demand have resulted to public institutions adjusting periodically. New technological development has pushed most governments to modernize their systems in order to address their citizens ' demands for reliable and efficient services. As such, the Huduma Program of Kenya was launched in 2013 as a framework through which, a variety of channels advancing citizen-centric public services are supported through the use of digital technology at one stop centres throughout the country. The purpose of the study is to examine the effect of Business Process Re-engineering on service delivery in Huduma centers in Kenya. Methodology: The methodology used by the researcher used both quantitative and qualitative through the administration of questionnaires that were used as a data collection tool to study a target population of 51 Huduma Centres across the 47 counties in Kenya and an entire population of 153 respondents working at the management level in all operational Huduma centres in Kenya. Hypotheses were tested using regression analysis and Pearson's Product Moment Correlation analysis. The study findings were presented in both tables and figures. Findings: the study findings revealed that the Huduma centers conduct frequent evaluations of their business processes that affect the delivery of public services they offer. Findings established that Business Process Reengineering practice has statistically significant effect on public service delivery with a p value (0.000) which was less than the conventional probability of 0.05 significance level. The results implied that business process re-engineering is a good predictor of service delivery. The findings have also recognized the role of business process re-engineering as a critical factor affecting one stop shop operations in Kenya. However, there is a need to re-examine the present processes involved, analyze them, and redesign them to be more efficient and cost-effective. These practices must be positive in character in order for citizens to easily use government services. As a conclusion, the results have addressed the knowledge gap in the administration of the Huduma Centres in Kenya. Unique Contributions to Theory, Practice and Policy: The study recommended that to enable institutions to redevelop their business procedures through the acknowledgement of which business processes are obsolete and can be eliminated, group related operations, substitute old machines with others, retain gangways and hold business sectors with high frequency.